PENINGKATAN PENGETAHUAN KADER POSYANDU DALAM PENERAPAN TEKNIK KONSERVASI ENERGI UNTUK MENINGKATKAN KUALITAS HIDUP KLIEN TUBERKULOSIS PARU - Ningning Sri Ningsih; Nieniek Ritianingsih; Farial Nurhayati (Poltekkes Kemenkes Bandung, 2022)
Tuberculosis is a chronic and recurrent infectious disease that attacks the lungs, caused by Mycobacterium tuberculosis. Patients with tuberculosis will experience impaired gas exchange, ineffective airway, changes in breathing patterns, lack of nutrition, and feelings of fear. With these conditions, the quality of life of tuberculosis sufferers will decrease. One of the treatments to improve the quality of life of tuberculosis clients is energy conservation techniques. This technique is useful for saving energy when the patient performs daily activities, by reducing dyspnea and increasing the patient's functional and social abilities. The purpose of this activity is to increase the knowledge of cadres about energy conservation techniques and cadres can disseminate to tuberculosis clients so that the quality of life of tuberculosis clients can increase. The method of this activity is carried out by teaching methods with lectures and practices on energy conservation techniques. The results of cadre knowledge activities for partners I in pre and II show that there is an effect of training on increasing knowledge of health cadres both for partner I and partner II (P = 0.00) and there is an effect of applying energy conservation techniques on the quality of life of tuberculosis patients in partner I. and partner II (P=0.00). The conclusion is that there is an increase in the knowledge of cadres about tuberculosis and conservation techniques so that cadres can carry out and assist tuberculosis patients. And the provision of energy conservation techniques to tuberculosis patients showed an increase in the quality of life into a good category. It is recommended that Cadres continue to assist and supervise the implementation of energy conservation techniques on a regular basis in their area.